Effect of anharmonicities in the critical number of trapped condensed atoms with an attractive two-body interaction - Filho, Victo S. [UNESP]; Gammal, Arnaldo [UNESP]; Tomio, Lauro [UNESP] (American Physical Society (APS), 2002)
The quantitative effect in the maximum number of particles and other static observables was determined. A deviation in the harmonic trap potential that is effective only outside the central part of the potential, with the addition of a term that is proportional to a cubic or quartic power of the distance was considered. Results showed that this study could be easily transferred to other trap geometries to estimate anharmonic effects.
Keywords: Algorithms; Approximation theory; Condensation; Harmonic analysis; Kinetic energy; Oscillators (mechanical); Quantum theory; Bose-Einstein condensation (BEC); Atomic physics